(9-6i)*m=m

Simple and best practice solution for (9-6i)*m=m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9-6i)*m=m equation:


Simplifying
(9 + -6i) * m = m

Reorder the terms for easier multiplication:
m(9 + -6i) = m
(9 * m + -6i * m) = m

Reorder the terms:
(-6im + 9m) = m
(-6im + 9m) = m

Solving
-6im + 9m = m

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-9m' to each side of the equation.
-6im + 9m + -9m = m + -9m

Combine like terms: 9m + -9m = 0
-6im + 0 = m + -9m
-6im = m + -9m

Combine like terms: m + -9m = -8m
-6im = -8m

Divide each side by '-6m'.
i = 1.333333333

Simplifying
i = 1.333333333

See similar equations:

| m=6/m | | x=0x | | 60=x-134 | | 8x^2-35x-38=0 | | (2x+3)(2x+3)+2x-3(2x-3)=(4x+6) | | 3(2x+8)=5(4x-6) | | Log(13)+log(15)=log | | ln(x+4)=1 | | 6*7-2=x | | 0.75(4x-1)=0.25(6x-1) | | 9-5(n+6)=32 | | 42-m=2m-3 | | D^4+5d^3+6D^2-4D-8=0 | | (D^4+5d^3+6D^2-4D-8)y=0 | | 4cosx^4-cosx^2+1=0 | | 5(4+x)-1=2(x+10)-4x | | 4x=120-2x | | 3x+2x=160 | | 800x=20 | | 21-x=67 | | 97=32+x | | X-41=77 | | (x-17)=24-13 | | 3(2x-2)-4x=8 | | 5x+4=40-8x | | 2x*x=200 | | 7x-9+3x=8x-3 | | -7=9-2z | | 5x-7+2x=6x+1 | | 2+x-5-2x-7=3x+7 | | 3y+7=2y+3 | | 2m(3M)=0 |

Equations solver categories